2021
DOI: 10.1371/journal.pone.0244381
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clinical and microbiota responses to fecal microbial transplantation in adult horses with diarrhea

Abstract: Background and aims Fecal microbial transplantation (FMT) is empirically implemented in horses with colitis to facilitate resolution of diarrhea. The purpose of this study was to assess FMT as a clinical treatment and modulator of fecal microbiota in hospitalized horses with colitis. Methods A total of 22 horses with moderate to severe diarrhea, consistent with a diagnosis of colitis, were enrolled at two referral hospitals (L1: n = 12; L2: n = 10). FMT was performed in all 12 patients on 3 consecutive days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 45 publications
(61 reference statements)
0
36
0
1
Order By: Relevance
“…Notably, three of the four foals received one to three fecal microbiota transplantations (FMT) during the course of diarrhea, which was considered effective in all cases. While the use of FMT in adult horses with diarrhea has been recently evaluated by means of NGS [73], to the authors knowledge, there is no peer-reviewed literature on the efficacy of FMT in neonatal foals [74]. McKinney et al (2021) reported that FMT proved an effective treatment to reduce diarrhea severity in horses with colitis and to improve microbiome diversity [73].…”
Section: Limitations and Potential Confounding Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, three of the four foals received one to three fecal microbiota transplantations (FMT) during the course of diarrhea, which was considered effective in all cases. While the use of FMT in adult horses with diarrhea has been recently evaluated by means of NGS [73], to the authors knowledge, there is no peer-reviewed literature on the efficacy of FMT in neonatal foals [74]. McKinney et al (2021) reported that FMT proved an effective treatment to reduce diarrhea severity in horses with colitis and to improve microbiome diversity [73].…”
Section: Limitations and Potential Confounding Factorsmentioning
confidence: 99%
“…While the use of FMT in adult horses with diarrhea has been recently evaluated by means of NGS [73], to the authors knowledge, there is no peer-reviewed literature on the efficacy of FMT in neonatal foals [74]. McKinney et al (2021) reported that FMT proved an effective treatment to reduce diarrhea severity in horses with colitis and to improve microbiome diversity [73]. While it is very likely that FMT had influenced the findings and represent a main confounding factor, an effect of FMT on fecal microbiota dynamic was not possible to be discriminated in this study.…”
Section: Limitations and Potential Confounding Factorsmentioning
confidence: 99%
“…A small 2014 study of horses with antibiotic-induced or undifferentiated colitis reported improved fecal consistency following FMT in three out of four recipients [29]. These results are supported by a larger and more recent study by McKinney et al, which assessed the clinical and microbiota responses to FMT in 12 hospitalized adult horses with colitis [55]. Prior to treatment, researchers found lower alpha-diversity and higher beta-diversity of the fecal microbiota of horses with colitis.…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 83%
“…In a similar vein, prebiotics are “substrate that is selectively utilized by host microorganisms conferring a health benefit” [ 53 ]. Based on the same principles, but taking a more comprehensive approach, FMT involves transfer of fecal suspension from a healthy donor to the bowel of a recipient [ 15 ], and successful applications in human medicine have understandably piqued interest in the veterinary community [ 29 , 54 , 55 ].…”
Section: The Appeal Of Microbiota Manipulationmentioning
confidence: 99%
“…This study by Caroline McKinney and co ‐ workers in the USA assessed faecal microbial transplantation (FMT) as a treatment and modulator of faecal microbiota in horses with colitis .…”
Section: Faecal Microbial Transplantationmentioning
confidence: 99%